PERANCANGAN CUSTOMER RELATIONSHIP MANAGEMENT PADA KLINIK (Studi Kasus: Klinik Pratama Nusa Medika Meritjan) - Yudo Bismo Utomo; Wing Wahyu Winarno; Armadyah Amborowati (Universitas Muhammadiyah Ponorogo, 2016)
Pratama Nusa Medika Clinic is a clinic that specialized in health services. This clinic requires a web-based CRM application to solve the problems in serving patients who still use manual processes. Before the CRM application is designed, the authors analyze the first to collect data and information using operational CRM and Gartner. Having analyzed then the application is designed and then produced a prototype based CRM website. Results obtained from this research is to implement a web-based CRM application in the clinic, can facilitate the clinic manage all business processes running, so established a good relationship between the patients with the clinic with twoway communication